1976
DOI: 10.1080/03014467600001431
|View full text |Cite
|
Sign up to set email alerts
|

The age of menarche in Nigerian girls

Abstract: The median ages at menarche were obtained from a sample of 2029 urban and 328 rural Nigerian girls by the status quo method, and calculated by probits. The median age at menarche for the urban girls was 13-70 +/- 0-03 years whilst it was 14-50 +/- 0-09 years for the rural girls. There were significant differences in the median menarcheal ages of the girls according to the level of education and the occupation of the parents, and their geographical residence. The number of siblings and the birth rank of the gir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 6 publications
3
29
0
Order By: Relevance
“…In Europe, similar patterns have been observed in a sample from Brussels (Susanne and Vercauteren, 1997), where the authors found no significant differences due to social background in age at menarche; in Greek girls (Papadimitriou et al, 1999) in the modern middle-class Athenian society, parental education did not influence age at menarche in middle-class Athens; in northeast England the same happened (Roberts et al, 1971(Roberts et al, , 1986. At present, some populations such as Poland (Bielicki and Welon, 1982;Bielicki et al, 1986;Laska-Mierezejewska, 1995) and many developing countries, for example, Khartoum (Sudan) (Attallah et al, 1983), Nigeria (Uche and Okorafor, 1979;Oduntan et al, 1976), Egypt (Attallah, 1978), Haiti (Barnes-Josiah and Augustin, 1995), and Venezuela (Farid-Coupal et al, 1981), showed a significant influence of parents' educational level and occupation. In France, Pasquet and Ducros (1980) found a significant influence of father occupation only between daughters of white-collar workers and farmers.…”
Section: Parents' Educational Level and Occupationmentioning
confidence: 76%
See 3 more Smart Citations
“…In Europe, similar patterns have been observed in a sample from Brussels (Susanne and Vercauteren, 1997), where the authors found no significant differences due to social background in age at menarche; in Greek girls (Papadimitriou et al, 1999) in the modern middle-class Athenian society, parental education did not influence age at menarche in middle-class Athens; in northeast England the same happened (Roberts et al, 1971(Roberts et al, , 1986. At present, some populations such as Poland (Bielicki and Welon, 1982;Bielicki et al, 1986;Laska-Mierezejewska, 1995) and many developing countries, for example, Khartoum (Sudan) (Attallah et al, 1983), Nigeria (Uche and Okorafor, 1979;Oduntan et al, 1976), Egypt (Attallah, 1978), Haiti (Barnes-Josiah and Augustin, 1995), and Venezuela (Farid-Coupal et al, 1981), showed a significant influence of parents' educational level and occupation. In France, Pasquet and Ducros (1980) found a significant influence of father occupation only between daughters of white-collar workers and farmers.…”
Section: Parents' Educational Level and Occupationmentioning
confidence: 76%
“…Socioeconomic status, often given by parents' educational level or occupation, has also shown a significant influence; girls of lower social origin on average exhibiting a delay in first menstruation compared with girls from well-off families. This was found in studies in Poland (Bielicki et al, 1986;Laska-Mierezejewska, 1995), in Hungary (Bodzsar, 1975), in Khartoum (Sudan) (Attallah et al, 1983), in Nigeria (Oduntan et al, 1976;Uche and Okorafor, 1979), in Egypt (Attallah, 1978), and South Africa (Henneberg and Louw, 1995). Family size and birth order also have shown a significant effect on age at menarche, with girls in large families exhibiting a delay of maturation (Roberts et al, 1971;Billewicz et al, 1981;Roberts, 1984, 1993;Clegg, 1980;Cameron and Nadgdee, 1996;Sánchez-Andrés, 1997;Apraiz, 1999).…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Due to improvements in the general pattern of living conditions, especially concerning health care and nutrition, age at menarche in Europe, North America, and other developed countries has shown a general downward trend (Eveleth and Tanner, 1990;Malina et al, 2004a). On the other hand, large differences among social class have been reported for the ''developing'' countries in Asia and Africa, where the gap between rich and poor is very large (Attallah et al, 1983;Oduntan et al, 1976;Uche and Okorafor, 1979).…”
mentioning
confidence: 99%